(untitled) (Clinics, 2014)
OBJECTIVE: To characterize the findings of behavioral hearing assessment in HIV-positive individuals who received and did not receive antiretroviral treatment. METHODS: This research was a cross-sectional study. The participants were 45 HIV-positive individuals (18 not exposed and 27 exposed to antiretroviral treatment) and 30 control-group individuals. All subjects completed an audiological evaluation through pure-tone audiometry, speech audiometry, and high-frequency audiometry. RESULTS: The hearing thresholds obtained by pure-tone audiometry were different between groups. The group that had received antiretroviral treatment had higher thresholds for the frequencies ranging from 250 to 3000 Hz compared with the control group and the group not exposed to treatment. In the range of frequencies from 4000 through 8000 Hz, the HIV-positive groups presented with higher thresholds than did the control group. The hearing thresholds determined by high-frequency audiometry were different between groups, with higher thresholds in the HIV-positive groups. CONCLUSION: HIV-positive individuals presented poorer results in pure-tone and high-frequency audiometry, suggesting impairment of the peripheral auditory pathway. Individuals who received antiretroviral treatment presented poorer results on both tests compared with individuals not exposed to antiretroviral treatment.